The moderating effect of individual culture orientation on the relationship between leadership styles with perceived employees performance on Banks of Pakistan - Fazal, Javeria (2013)
The purpose of this study is to examine the relationship of leadership styles and perceived employee performance and further explores the moderating effect of individual culture orientation, such as power distance, uncertainty avoidance, masculinity and individualism on the relationship of transformational leadership and perceived employee performance in banking sector of Pakistan. This empirical study explains the role of two types of leaders, transformational leader who unite the interests of organization and its members in contrast with the transactional leader who practice contingent reinforcement of followers. Transformational leadership styles build on the transactional base in contributing to the extra effort and performance of followers. Therefore, the study also examines that which leadership style is more authentic and influential. Data from 127 subordinates indicates significant and positive association of transformational and transactional leadership with perceived employee performance. In addition, results indicate that transformational leadership has stronger and positive association with perceived employee performance. Regarding the moderating effects of culture orientation, overall data shows significant influence on the relationship of leadership styles and perceived employee performance. The findings have important implications for the organization and leadership literature